SEVERITY OF PROGENY SELECTION FROM DIALLEL CROSSING OF PEA (PISUM SATIVUML) - I. M. Kaigorodova; O. N. Pishnaya; E. P. Pronina (Овощи России, 2015)
The promising pea varieties for canning with an optimum combination of elements of yield production have been selected based on utilization of geographically dispersed and morphologically different forms in progeny of diallel crossing. A comparative evaluation of the severity selection in different hybrid generations is shown, from which conclusions are drawn about the breeding value of parental forms.